Some Considerations about the Economic Problems Generated by Hypertrophication in the Romanian Shore Area of the Black Sea - Leonard Magdalin Dorobăț; Anca Turtureanu; Codruța Mihaela Dobrescu (Journal of Danubian Studies and Research, 2020)
The hypertrophication phenomenon (excessive eutrophication, induced by human activities) affects more and more the waters in the western area of the Black Sea, including the Romanian sector. This phenomenon is generated by the accumulation, in large volumes, in the sea waters, of some compounds, especially phosphorus, nitrous and nitrates, which mainly originate in the agriculture made in the river basin of the Black Sea, and from certain industrial activities, as well as from the household waters reaching the flowing waters that are tributary to the Danube. Romanian sea waters are affected by the transport of these compounds mainly by the Danube, but also by the ones coming from the Dniester and the Dnieper. There is a common responsibility for the fact that these phosphorus and nitrous compounds, which generate the hypertrophication in the waters of the Black Sea, belonging to all the states from the river basin of the three large flowing waters, to a larger or smaller extent, which is frequently hard to quantify. The negative economic impact consists of the more and more frequent pollution with algae of the sea water and beaches in the Romanian area, disturbing phenomenon which even banishes tourists. Then, the changes in the biocoenosis structure also lead to loses in aquaculture and fishing. It is necessary to implement a system to identify polluters, to quantify the amount of pollution of each involved part to share the costs between them.